APLIKASI KOMPOS JERAMI PADI DAN PUPUK P TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KEDELAI (Glycine max L. Merrill) - Rizki Darmawan; Adiwirman Adiwirman; Isna Rahma Dini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This study aims to determine the interaction of rice straw compost and P fertilizer on the growth and yield of soybean plants (Glycine max (L.) Merril). This research was conducted in the experimental station of the Faculty of Agriculture, Riau University, starting from June to October 2017. This study used a Randomized Block Design (RBD) consisting of 2 factors and 3 replications. The first factor was the dose of rice straw compost (K) consisting of K0: without the provision of rice straw compost, K1: Compost rice straw with a dose of 5 tons. Ha-1, K2: Compost rice straw with a dose of 10 tons. Ha-1, K3 : Compost Rice straw with a dose of 15 tons. Ha-1. The second factor is the dose of TSP fertilizer (P) which consists of P1: TSP 300 kg. Ha-1, P2: TSP 326 kg. Ha-1. The results of this study indicate that rice straw compost increases the growth and yield of soybean plants. Compost of rice straw can increase plant height, number of rice pods, total number of pods, yield per plot and weight of 100 seeds. Application of P fertilizer does not increase the growth and yield of soybean plants. The interaction of rice straw compost and P fertilizer did not increase the growth and yield of soybean plants. Keywords: Soybeans, rice straw compost, TSP fertilizer